?SIMULATION OF CHLORIDE TRANSPORT BASED DESCRIPTIVE SOIL STRUCTURE (Biological Sciences - PJSIR, 2003)
There is a need of environmental implications of rapid appearance of surface by applying chemical at depths below the vadose zone (tile line or shallow groundwater) for developing better insight into solute flow mechanism through the arable lands. Transport of chloride, a respresentative non-adsorbing solute, through a moderately structured silty clay loam soil (Gujranwala series, Typic Ustochrepts) and an un-structured sandy loam soil (Nabipur series, Typic Camborthid) was characterized and two existing models viz. convection dispersion equation (CDE) and preferential flow models were tested. The flux average of solute concentration in the outflow as a function of cumulative drainage was fitted to the models. The CDE fitted, relatively, better in the non-structured soil than in the moderately structured soil. Dispersivity value deter- mined by CDE was very high for the structured soil which is physically not possible. The preferential flow model fitted well in the Gujranwala soil, but not in the Nabipur soil. The breakthrough characteristics i.e. drainage to peak concentration (Dp), symmetry coefficient (SC), skewness, and kurtosis were compared. Chloride breakthrough was earlier than expected based on piston flow. It indicated preferential flow in both the soils, yet, immediate appearance of the tracer in the Gujran- wala soil demonstrated even larger magnitude of the preferential flow. Breakthrough curves’ parameters indicated a large amount of the solute movement through the preferred pathways bypassing the soil matrix in the Gujranwala soil. The study suggests that some soil structure parameters (size/shape and degree of aggregation) should be incorporated in the solute transport models.